On the eigenvalue problems for differential operators with coupled boundary conditions - Sajavičius, S. (Nonlinear Analysis: Modelling and Control, 2010)
In the paper, the eigenvalue problems for one- and two-dimensional second order differential operators with nonlocal coupled boundary conditions are considered. Conditions for the existence of zero, positive, negative or complex eigenvalues are proposed and analytical expressions of eigenvalues are provided.